Numerical modelling of the transitive and established processes in electric circuits with variable parameters - Rimsky V.X.; Berzan V.P.; Patsiuk V.I. (Problems of the Regional Energetics, 2008)
Analytical and numerical approaches to the analysis of the transitive and established processes in electric circuits with the distributed and concentrated parameters are stated. Influence of losses on dynamics of instant values of voltage and currents in a mode of idling is investigated and at short circuit of lines of half-wave and quarter wave length.